BLOOD LIPID DISORDER IN MEN WITH INCREASED WAIST CIRCUMFERENCE COMPARED TO MEN HAVING NORMAL WAIST CIRCUMFERENCE WITHIN THE SAME CATEGORY OF BMI - Faour, Tarek; Hassan, Khodor Haidar; Ghanem, Zizi M.; Atta-Alla, Ahmed E.S.; Ghanem, Ricardos; Abdallah, Rony; Semaan, Pierre; Nasser, Roudaina; Berry, Fadwa; Ezzedine, Mohamad; et al. (European Scientific Journal, ESJ, 2015)
Background: No local studies have been performed yet to investigate the influence of central or abdominal obesity on serum lipids in men having increased Waist Circumference (WC) compared to men with normal Waist Circumference values within the same BMI (Body Mass Index) category. Objective:To examine whether the prevalence of dyslipidemia, (defined as Hypercholesterolemia (Total Cholesterol level ≥240 mg/dl), high LDL-C level (≥160 mg/dl), low HDL-C level (<35 mg/dl), or Hypertriglyceridemia (TG level ≥200 mg/dl)), is higher in men having high Waist Circumference compared to others with normal WC values within the same BMI category. Methods: The study was conducted between September 2013 and July 2014. Eighty-eight overweight men (BMI = 25-29.9) were grouped by WC as follows: 28 with high values (>102 cm) and 60 with normal values (≤ 102cm). Blood samples were drawn and assayed for total cholesterol, triglyceride, HDL-C, and LDL-C,at the department of Laboratory in the Faculty of Public Health, Lebanese University. All assays were performed by enzymatic colorimetric methods using Hitachi-704. Results: Overweight men with high WC values (according to cutoff points internationally adopted) were the most likely to have dyslipidemia with its subsequent increased health risk compared with those having normal WC values. Conclusion: we showed in this study that the prevalence of dyslipidemia in men with high WC values is greater compared to those with normal WC values within the same BMI category. This finding leads us to the importance of the incorporated evaluation of WC in addition to the BMI in clinical practice.